Evolutionary loss of complexity in animal signals: cause and consequence. (14th December 2022) - Ord, Terry J; Diesmos, Arvin; Ahmad, Norhayati; Das, Indraneil
Abstract: We identified hypotheses for the cause and consequences of the loss of complexity in animal signals and tested these using a genus of visually communicating lizards, the Southeast Asian Draco lizards. Males of some species have lost the headbob component from their display, which is otherwise central to the communication of this genus. These males instead display a large, colorful dewlap to defend territories and attract mates. This dewlap initially evolved to augment the headbob component of the display, but has become the exclusive system of communication. We tested whether the loss of headbobs was caused by relaxed selection, habitat-dependent constraints, or size-specific energetic constraints on display movement. We then examined whether the consequences of this loss have been mitigated by increased signaling effort or complexity in the color of the dewlap. It appears the increased cost of display movement resulting from the evolution of large body size might have contributed to the loss of headbobs and has been somewhat compensated for by the evolution of greater complexity in dewlap color. However, this evolutionary shift is unlikely to have maintained the complexity previously present in the communication system, resulting in an apparent detrimental loss of information potential.